Therapeutic opportunities for improving the course of coronavirus disease and reducing the frequency of gestional complications - V.V. Kaminskyi; R.O. Tkachenko; A.V. Kaminskyi; O.I. Zhdanovych; L.I. Vorobei; T.V. Kolomiichenko; O.I. Gervaziuk; R.R. Tkachuk; S.I. Mudryi (Publishing House TRILIST, 2021)
Research objective: to study the clinical efficacy of the proposed treatment complex in pregnant women with coronavirus disease (COVID-19). Materials and methods. 60 pregnant women with a moderate COVID-19 who were treated at the Kyiv City Center for Reproductive and Perinatal Medicine were examined and selected to assess the effectiveness of the proposed treatment. Pregnant women were divided into 2 clinical groups: the main group (n = 30) were prescribed treatment complex with progestin, the comparison group consisted of 30 pregnant women with COVID-19, who did not differ in age, sex, body mass index and received only standard drug therapy. Given the immunomodulatory effect, micronized progesterone was administered orally 200 mg three times a day immediately after hospitalization for 2 weeks, regardless of gestational age. Clinical manifestations, laboratory and instrumental indicators, duration of oxygen therapy and respiratory support, duration of hospital stay and intensive care were analyzed to assess the treatment complex. Results. Therapeutic complex with progesterone helps to reduce the severity of respiratory disorders in pregnant women with COVID-19, the general condition of pregnant women improves faster and inflammatory changes in the lungs regress. The positive dynamics of pulse oximetry indicators was noted. The frequency of the additional methods of respiratory support and transfer to the intensive care unit were lower, and a more rapid normalization of laboratory parameters was noted. Incidence of gestational complications (threats of pregnancy termination, placental insufficiency, fetal growth retardation and distress, oligohydramnios, premature birth and premature rupture of membranes) was lower against the background of treatment with progesterone, children status was better at birth. The need for oxygen therapy, the length of stay in the intensive care unit and the total length of hospitalization are significantly reduced when progesterone was prescribed for pregnant women with COVID-19. Conclusions. The use of progesterone in pregnant women with coronavirus disease has a stabilizing effect, has no negative side effects which is significantly expands the scope of the proposed therapy in pregnant women at different stages of gestation.